A prospective study on dinghy sailors` training habits and injury incidence with a comparison between elite sailor and club sailor during a 12-month period - Bøymo-Having, L.; Grävare, M.; Grävare Silbernagel, K. (British Journal of Sports Medicine, 2013)
Background: Sailing is an Olympic sport practiced by both men and women of all ages. Despite being a popular sport, we have found no prospective studies investigating the injury incidence and training quantity such as found for other sports. The purpose of this study was to do an inventory over dinghy sailors` training habits, injury incidence and type of injury.